2015
DOI: 10.1002/bdrc.21090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal diabetes on the embryo, fetus, and children: Congenital anomalies, genetic and epigenetic changes and developmental outcomes

Abstract: Tight metabolic control, surveillance, and labor management remain the cornerstone of care for pregnant women with diabetes, but advances in the field indicate that new treatments to protect the mother and baby are not far from becoming clinical realities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(212 citation statements)
references
References 191 publications
(204 reference statements)
5
203
0
4
Order By: Relevance
“…Epidemiological studies have identified significant environmental risk factors for human CHD, including maternal exposures to alcohol, isotretinoin, thalidomide, antiseizure medications, antiretroviral medications, environmental teratogens and infectious agents. Embryo hypoxia is another well-recognized risk factor caused by smoking, living at high altitude, maternal diabetes, high body mass index, hypertension or prescription medications (Watkins et al, 2003;Jenkins et al, 2007;Zheng et al, 2013;Webster et al, 2014;Ornoy et al, 2015;Ramakrishnan et al, 2015;Sullivan et al, 2015). The specific effects of environment on embryonic development have been studied by exposing pregnant animals to a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have identified significant environmental risk factors for human CHD, including maternal exposures to alcohol, isotretinoin, thalidomide, antiseizure medications, antiretroviral medications, environmental teratogens and infectious agents. Embryo hypoxia is another well-recognized risk factor caused by smoking, living at high altitude, maternal diabetes, high body mass index, hypertension or prescription medications (Watkins et al, 2003;Jenkins et al, 2007;Zheng et al, 2013;Webster et al, 2014;Ornoy et al, 2015;Ramakrishnan et al, 2015;Sullivan et al, 2015). The specific effects of environment on embryonic development have been studied by exposing pregnant animals to a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that gestational diabetes can lead to adverse metabolic outcomes for both the mother and the child [12,13,14]. Our previous report established that FFA2 is involved in maintaining gestational glucose homeostasis [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the long-term, it increases the likelihood that the mother will develop type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD), and metabolic syndrome [13]. Similarly, maternal hyperglycemia during pregnancy places the offspring at increased risk for T2DM, obesity and metabolic syndrome [14]. Therefore, we first explore if maternal hyperglycemia during pregnancy due to Ffar2 deletion is sufficient to lead to aberrant metabolic health in their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The autism genes are also expressed and enriched in the pancreas and this is relevant to associations between maternal diabetes and autism (Ornoy et al, 2015). The autism genes are also expressed and enriched in the adrenals which secrete many steroid hormones (e.g.…”
Section: Glandular Expression and Enrichment Of The Autism Genesmentioning
confidence: 99%